Impact of ICT latency, data loss and data corruption on active distribution network control - Klaes, Marcel; Zwartscholten, Jannik; Narayan, Anand; Lehnhoff, Sebastian; Rehtanz, Christian (Technische Universität Dortmund, 2023)
The ongoing changes in modern power systems towards increasingly decentralized systems render the coordination of generation assets and the corresponding dependency on Information and Communication Technology highly relevant. This work demonstrates the impact of three types of ICT errors, namely delayed data, data loss and data corruption, on the control of distributed energy resources in an active distribution network. The settling time of the active power response at the interconnection point between the distribution and transmission system is investigated in the simulations. Additionally, two fallback strategies to mitigate the impact of data loss are proposed and evaluated with regard to their impact on the controller’s response. Finally, a generalized, aggregated service state description is proposed in order to capture the performance of the active distribution network service. It is meant to improve the interpretability of the results, which can be used to compare service designs and setups.
IEEE access;11
Keywords: Active distribution network control; performance of service; corrupted data; delayed data; service states; unavailable data; 620